Pragmatism, Persuasion, and Force in Bhimrao Ambedkar's Reconstruction of Buddhism - Stroud, Scott R. (The journal of religion, 2017)
The article presents an analysis of politician Bhimrao Ambedkar's views on reconstruction of Buddhism and its relevance for communism. Topics discussed include negative impact of communism on religious systems of all countries, relevance of Buddhism for Indian tradition and civil rights leaders such as Mahatma Gandhi and social oppression and exclusion faced by Ambedkar being religiously grounded in Hindu shastras and traditions.